Chat GPT and AI Applications as Islamic Religious Education Learning Assistants - Husniyatul Ariibah; Ary Asyari (Ngaji: Jurnal Pendidikan Islam, 2025)
Education in the modern era has undergone a significant transformation along with the advancement of digital technology. Digital technologies that are currently popularly applied in the field of education are ChatGPT and AI (Artificial Intelligence)  applications as interactive and responsive learning assistants. This study aims to examine how the use of ChatGPT and AI applications is used wisely as learning assistants. The research employs a qualitative, literature-based approach and is analyzed through content analysis. The data of this research was taken from various literature sources such as scientific articles, books, and other relevant references. The results of this study show that the application of ChatGPT and AI in Islamic Religious Education (PAI) can improve the quality and effectiveness of learning through blended learning models and artificial intelligence applications through features such as visual mentors, voice assistants, and translator presenters. However, during implementation, several challenges remain, including limitations in digital infrastructure, low digital literacy among teachers, and concerns about the accuracy and authenticity of religious content. Wise strategies need to be carried out to improve digital literacy, verify information generated by AI, instill ethics, and conduct supervision. ChatGPT and AI applications have a positive impact, such as increasing students' motivation and interest in learning. But it also has negative impacts such as technology dependence, lowering academic integrity, and plagiarism. Therefore, the use of ChatGPT and AI applications needs to be done carefully and responsibly.